(untitled) (International Journal of Food and Nutritional Sciences, 2019)
In most developing nations, rising unemployment has replaced falling living standards as the primary barrier to poverty. As a result of the per capita income’s sharp decline, the poor are getting poorer. Even those who are literate struggle to make enough money to meet their requirements and are either underemployed or unemployed.